Ontology driven platform for tourism insights in Malaysia - Izani, Ummi Maisarah; Che Lah, Nur Syadhila (Universiti Teknologi MARA, Perak, 2025)
Tourism in Malaysia is characterized by its cultural diversity, rich heritage, and a wide range of experiences spanning from local attractions to unique culinary offerings. However, fragmented data sources and lack of semantic integration often hinder tourists and stakeholders from gaining meaningful insights. This research presents a digital ontology-driven platform designed to unify and contextualize tourism-related information through a structured knowledge representation framework. The proposed ontology model captures and interlinks key tourism domains including local attractions and food options, enabling intelligent query processing, personalized recommendation, and contextual awareness. This research follows the CRISP-DM methodology, ensuring a structured approach from data collection and preprocessing to ontology modelling and visualization. By leveraging ontology based reasoning and semantic relationships, the platform supports enhanced decision making for both tourists and tourism authorities. A prototype dashboard is developed to visually demonstrate tourism insights, offering users an intuitive interface to explore categorized information based on location, preference, and service availability. This integrated approach aims to support Malaysia’s smart tourism initiatives and elevate the digital experience for both domestic and international travellers.